An Evaluation Study of the Merdeka Curriculum Lesson Plan in Islamic Elementary School - Erdiyanti; Kharis Sulaiman Hasri; Ahmad Hilmi; Yeni Wulandari (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Many experts have conducted studies on lesson plans, but research evaluating the Merdeka Curriculum lesson plan using Stake theory is still limited. This study examined teachers’ understanding of the Merdeka Curriculum lesson plan, the process of developing it, and the teaching module documents they created. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation at State Islamic Elementary School (MIN) 2 Konawe Selatan. The participants consisted of two teachers and one principal. Data validity was tested using time and technique triangulation. Data analysis techniques followed the Miles and Huberman procedure, which consists of three stages: data reduction, data presentation, and conclusion drawing. The results showed that teachers have a deep understanding of the Merdeka Curriculum. They used the ATM (Observe, Imitate, Modify) approach in creating lesson plans and adapting them to the local context. However, improvements were still needed in the use of technology and learning media. Most of the prepared learning module documents met the established standards, although some components still need improvement. The implications of this study highlight the importance of teacher training and competency development, as well as educational policies that support the use of technology in lesson planning. These findings provide valuable insights for improving the quality of education in Indonesia, particularly in the implementation of the Merdeka Curriculum.